A New Nano-Platform of Erythromycin Combined with Ag Nano-Particle ZnO Nano-Structure against Methicillin-Resistant Staphylococcus aureus - Atanu Naskar; Sohee Lee; Yunhee Lee; Semi Kim; Kwang-sun Kim (MDPI AG, 2020)
Nano-particles have been combined with antibiotics in recent studies to overcome multidrug-resistant bacteria. Here, we synthesized a nano-material in which Ag nano-particles were assembled with a ZnO nano-structure to form an Ag-ZnO (AZO) nano-composite at low temperature. This material was combined with erythromycin (Ery), an antibiotic effective towards gram-positive bacteria, using three different approaches (AZO + Ery (AZE) [centrifuged (AZE1), used separately after 1-h gap (AZE2), without centrifugation (AZE3)]) to prepare a nano-antibiotic against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA). X-ray diffraction analysis and transmission electron microscopy confirmed the presence of Ag nano-particles and ZnO nano-structure. The elemental and chemical state of the elements present in the AZO nano-composite were assessed by X-ray photoelectron spectroscopy. The antibacterial activity of AZE samples against both Escherichia coli and S. aureus strains including MRSA was evaluated in antibacterial and morphological analyses. The AZE3 sample showed greater antibacterial activity than the other samples and was comparable to erythromycin. AZE3 was ~20-fold less prone to developing bacterial resistance following multiple exposures to bacteria compared to erythromycin alone. The AZE3 nano-composite showed good biocompatibility with 293 human embryonic kidney cells. Our newly synthesized nano-platform antibiotics may be useful against multidrug-resistant gram-positive bacteria.